2. The Openness of the Visual Art Curriculum towards a New Visual Art Language - Aprotosoaie-Ifti (Sciendo, 2016)
Visual art curriculum should allow a wide range of activities to develop children's imagination and creativity, to provide a balanced framework for the harmonious development of people who can cope with the massive ammount of images that invade our daily lives. Contemporary art develops a new language - a hybrid language - which for now remains unknown to the majority of the public and it is not integrated into the Arts curriculum. General frame analysis reveals that Fine Arts are studied only up to the 10th grade, except for the humanity profile and for the vocational arts profile. School curricula stipulate fine arts study up to mid twentieth century. Openness towards contemporary art and the language of art starting with the second half of the twentieth century is quite limited even if the curriculum allows a certain flexibility in the approach.